Teach them and let them go flying … supporting secondary students who have a talent for Biology in our school (Training and Practice : Journal of Educational Sciences, 2019)
Discovering, teaching and supporting talents are of high priority in every human community as their future can be greatly influenced by their way of thinking, activities, and works. Teachers have been paying attention to talented children ever since schools exist. We teachers and the schools have to carry the biggest responsibility. In 2008 the Hungarian Parliament voted uniformly for initiating the National Talent Program which was a breakthrough in supporting talents in Hungary. The beginner teachers at that time support their younger colleagues nowadays with their own profession of faith rising to the occasion. Teams of subject teachers and talent groups have been created where they share good practices with each other. The Arany János Primary and Secondary School in Százhalombatta is a complex and multifaceted institution whose talent program was started by the introduction of the Zsolnai method in 1986. Its profile has expanded and changed in the more and more permissive educational environment. In 2001 we started teaching Science (Biology and Chemistry) at an advanced level for the 9th-grade students in our eight-year-long secondary education. In 2014 the National Core Curriculum was modified and obligatory framework curriculum was introduced. Since then only Biology is taught in phasing out system. In addition to the compulsory lessons, we put great emphasis on extra-curricular activities that contribute to talent support. In my article, I would like to present the development of our institution and the proven teaching practices in the field of our biological education.